Public-Private Partnerships: When Ethics and Policy Making are an Afterthought - Nathalie Burlone (Revue Gouvernance, 2006)
The interest of governments in public-private partnerships (P3s) has increased in the last decade. In Canada, this fervor is no exception; decision makers recognize an ideal tool of governance, in the logic of the “new public management.” While academic literature has focused on the actual benefits or problems associated with this form of service delivery - namely cost calculations, risk sharing, contract duration and efficiency - little attention has been paid to the ethical character of this policy instrument. As far as public management in general is concerned, ethics is generally an afterthought (Ghere, 1996). Where P3s are concerned, this quote is even more relevant. Given the efficiency mantra at the heart of P3s as a new policy instrument, it is no wonder that questions of values and public interest come second to promised or expected financial savings sought by political leaders. In order to tackle the role of ethics in public-private partnerships, this article takes a policy formulation stance and stresses the conflicts of values at the heart of this political choice and the challenges it involves for public interest and policy making in the long run.